Efficacy and safety of propranolol for treatment of temporomandibular disorder pain: a randomized, placebo-controlled clinical trial. Issue 8 (August 2020) - Tchivileva, Inna E.; Hadgraft, Holly; Lim, Pei Feng; Di Giosia, Massimiliano; Ribeiro-Dasilva, Margarete; Campbell, John H.; Willis, Janet; James, Robert; Herman-Giddens, Marcus; Fillingim, Roger B.; Ohrbach, Richard; Arbes, Samuel J.; et al.
Abstract : Abstract: Propranolol is a nonselective beta-adrenergic receptor antagonist. A multicenter, randomized, double-blind, placebo-controlled, parallel-group, phase 2b trial enrolled participants aged 18 to 65 years with temporomandibular disorder myalgia to evaluate efficacy and safety of propranolol compared with placebo in reducing facial pain. Participants were randomized 1:1 to either extended-release propranolol hydrochloride (60 mg, BID) or placebo. The primary endpoint was change in facial pain index (FPI = facial pain intensity multiplied by facial pain duration, divided by 100). Efficacy was analyzed as a mean change in FPI from randomization to week 9 and as the proportion of participants with ≥30% or ≥50% reductions in FPI at week 9. Regression models tested for treatment-group differences adjusting for study site, sex, race, and FPI at randomization. Of 299 participants screened, 200 were randomized; 199 had at least one postrandomization FPI measurement and were included in intention-to-treat analysis. At week 9, model-adjusted reductions in mean FPI did not differ significantly between treatment groups (−1.8, 95% CL: −6.2, 2.6; P = 0.41). However, the proportion with a ≥30% reduction in FPI was significantly greater for propranolol (69.0%) than placebo (52.6%), and the associated number-needed-to-treat was 6.1 ( P = 0.03). Propranolol was likewise efficacious for a ≥50% reduction in FPI (number-needed-to-treat = 6.1, P = 0.03). Adverse event rates were similar between treatment groups, except for more frequent fatigue, dizziness, and sleep disorder in the propranolol group. Propranolol was not different from placebo in reducing mean FPI but was efficacious in achieving ≥30% and ≥50% FPI reductions after 9 weeks of treatment among temporomandibular disorder participants. Abstract : Supplemental Digital Content is Available in the Text.In this randomized controlled trial in patients with chronic temporomandibular disorder, propranolol was not different from placebo in reducing the mean value of the primary outcome measure, a facial pain index representing the product of pain intensity and pain duration.